Diabetic Dead-in-Bed Syndrome: A Possible Link to a Cardiac Ion Channelopathy - Jonathan R. Skinner; Renate Marquis-Nicholson; Alix Luangpraseuth; Rick Cutfield; Jackie Crawford; Donald R. Love (Case Reports in Medicine)
Sudden unexpected nocturnal death among patients with diabetes occurs approximately ten times more commonly than in the general population. Malignant ventricular arrhythmia due to Brugada syndrome has been postulated as a cause, since a glucose-insulin bolus can unmask the Brugada electrocardiographic signature in genetically predisposed individuals. In this report we present a 16-year-old male with insulin-dependent diabetes who died suddenly at night. His diabetes had been well controlled, without significant hypoglycaemia. At autopsy, he had a full stomach and a glucose level of 7 mmol/L in vitreous humor, excluding hypoglycaemia. Genetic analysis of autopsy DNA revealed a missense mutation, c.370A>G (p.Ile124Val), in the GPD1L gene. A parent carried the same mutation and has QT prolongation. Mutations in this gene have been linked to Brugada syndrome and sudden infant death. The patient may have died from a ventricular arrhythmia, secondary to occult Brugada syndrome, triggered by a full stomach and insulin. The data suggest that molecular autopsies are warranted to investigate other cases of the diabetic dead-in-bed syndrome.